Legal Implications Following the Constitutional Court Decision No. 24/PUU-XX/2022 and the Supreme Court Circular No. 2 of 2023 Regarding the Prohibition for Courts to Grant Marriage Registration Requests Across Different Religions: Implikasi Hukum Pasca Keluarnya Putusan Mahkamah Konstitusi Nomor 24/PUU-XX/2022 dan Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 tentang Larangan Pengadilan untuk Mengabulkan Permohonan Pencatatan Perkawinan Beda Agama - Siarill, Jonathan Hervine; Djaja, Benny (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Interfaith marriage in Indonesia remains a complex legal issue due to the intertwining of religious norms and state administrative authority. Specific Background: The Constitutional Court Decision No. 24/PUU-XX/2022 and Supreme Court Circular No. 2/2023 further restrict court-granted registration of interfaith marriages by reaffirming the primacy of religious validity. Knowledge Gap: Despite extensive debate, limited research analyzes the combined legal, administrative, and human rights implications arising from both instruments. Aims: This study examines the legal consequences of the Court’s decision and the Circular, focusing on their impact on legal certainty, constitutional rights, and the status of interfaith families. Results: Using a normative juridical approach, the findings show that delegating substantive validity to religion and limiting administrative registration creates legal uncertainty, a regulatory vacuum, and discriminatory outcomes affecting marital status, children’s rights, inheritance, and civil documentation. Novelty: This research offers an integrated assessment of constitutional, administrative, and human rights dimensions, highlighting normative dissonance between constitutional guarantees and religion-based administrative practices. Implications: The study underscores the need for regulatory harmonization and proposes exploring civil marriage mechanisms to ensure legal certainty, equality before the law, and protection of fundamental rights within Indonesia’s pluralistic society. Highlights: Highlights the legal vacuum created by relying solely on religious validity for marriage recognition. Emphasizes the conflict between constitutional guarantees and restrictive administrative practice. Proposes civil marriage as a potential solution to ensure equal legal protection. Keywords: Interfaith Marriage, Legal Certainty, Constitutional Rights, Administrative Law, Human Rights